2014
DOI: 10.4236/ijcm.2014.519150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music on State of Ischaemia in Stable Angina; a Randomized Controlled Trial

Abstract: Introduction: Ischaemic heart disease is the number one cause of deaths in the world. As these patients experience severe distress due to a number of associated reasons, it is important to focus on both physiological and psychological needs of the patients in the management. Beyond the standard medical and surgical treatments, relaxation therapies such as relaxing music have been identified as having impact in reducing morbidity in ischaemic heart disease. Even though several studies have been conducted to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Moreover, from our study, no adverse effects due to music listening for a prolonged period were observed and hence this also confirms the current evidence of safety of relaxation music in therapeutic use [14]. This perceived improvement of the QoL in stable angina patients may be due to the significant improvement of severity of symptoms and the state of ischaemiaas observed in the previous parallel studies [18] [19] and hence the effect of music on underlying pathophysiology of myocardial ischaemia. Therefore, this would further help the scientists to understand the pathophysiological phenomenon of the effect of relaxing music.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, from our study, no adverse effects due to music listening for a prolonged period were observed and hence this also confirms the current evidence of safety of relaxation music in therapeutic use [14]. This perceived improvement of the QoL in stable angina patients may be due to the significant improvement of severity of symptoms and the state of ischaemiaas observed in the previous parallel studies [18] [19] and hence the effect of music on underlying pathophysiology of myocardial ischaemia. Therefore, this would further help the scientists to understand the pathophysiological phenomenon of the effect of relaxing music.…”
Section: Discussionsupporting
confidence: 90%
“…As this was an extension of two studies published [18] [19], the base line data were same as mentioned in the Table 1 of the previous research [19]. Both groups were approximately similar in the measured socio demographic variables.…”
Section: Baseline Datamentioning
confidence: 81%
See 1 more Smart Citation
“…Cancer patients experience pain, anxiety, and low mood, together with symptoms of related sympathetic overactivity (such as raised pulse rate, blood pressure, pupillary size, and respiratory rate). [1920212223] Our study aimed to fill the gap in knowledge about the potential effect of culturally appropriate instrumental classical music on the alleviation of these symptoms and signs among a cohort of cancer patients in Sri Lanka.…”
Section: Aimsmentioning
confidence: 99%
“…The effects of relaxing music are reducing stress hormones, metabolic rate, heart rate, blood pressure, free fatty acids, and oxygen consumption through neurophysiological mechanism. These effects include reducing the severity of the disease [ 24 ]. Moreover, studies have shown that participants’ physiological factors such as heart rate, blood pressure, and respiratory rate were decreased as a result of maintaining pleasant activities in daily life [ 25 ].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%